The Tradition of Dowry Through the Lens of Postcolonial Feminism in Brides Are Not for Burning - Molina Concha, Tania Valeria (2025)
Indian feminist theatre has produced unique dramatic expressions that have transcended the theatrical sphere. The themes addressed by various playwrights have given rise to social activism that fights to defend Indian women from gender-based violence. Dina Mehta’s play Brides Are Not for Burning (1979) deals with an issue that is still relevant today: death by dowry. In this context, it is important to analyze the theatrical text from the theoretical framework of gender studies, particularly postcolonial feminism. On the other hand, the study of the play refers exclusively to the dramatic text, due to the impossibility of staging the play (because Indian plays are not studied or performed in Argentina). For this reason, a hybrid methodology encompassing Western and Indian theorists is used in order to analyze the text in its entirety.